A Rational Theology, as Taught by the Church of Jesus Christ of Latter-Day Saints - Widtsoe, John Andreas, 1872-1952 (Salt Lake City, UT : Project Gutenberg, 2011)
"A Rational Theology, as Taught by the Church of Jesus Christ of Latter-day Saints" by John A. Widtsoe is an exposition of theological principles written in the early 20th century. The work aims to articulate the tenets of rational theology as understood by members of the Church of Jesus Christ of Latter-Day Saints, emphasizing a framework grounded in human knowledge, reason, and experience. The book seeks to present a coherent and logical philosophical interpretation of religious doctrines without delving into arguments, allowing readers to perceive the compatibility of the Gospel with established truths. The beginning of the book outlines the concept of rational theology, emphasizing the need for a framework that aligns with man's understanding and experiences. It serves as an introduction to themes such as the nature of man in the universe, how knowledge is obtained, and the fundamental principles that govern existence. It posits that the pursuit of knowledge is integral to formulating a satisfactory religion and underscores the idea that the principles of the Gospel are rooted in universal laws that can enhance daily life. This foundation sets the stage for deeper explorations into topics like God's nature, man's agency, and the relationship between human beings and divine wisdom, inviting readers to engage with and reflect on the interconnectedness of faith and rationality. (This is an automatically generated summary.)
Release date is 2011-03-12
Produced by the Mormon Texts Project. Volunteers: Benjamin Bytheway, Byron Clark, Ben Crowder, Tom DeForest, Eric Heaps, Jason Hills, Tod Robbins
Keywords: Theology; Latter Day Saint churches -- Doctrines; Church of Jesus Christ of Latter-day Saints -- Doctrines